Development of Technology Transfer Model with Enabling Performance Factors for the Libyan Petroleum Industry - Mohamed, Al Mabruk S. (2010)
Technology Transfer (TT) is increasingly being used on petroleum industry. The evaluation of TT significant indicators and their effect on TT performance for Libyan petroleum industry were investigated. The study main objective is to develop a TT model for the Libyan oil industry with performance factors. This study defined four categories of enabling factors that could have an effect on the TT process and its results for the petroleum industry: TT support, TT infrastructure, industry learning capability, and TT environment. The resultant TT performance and the relationship between enabling and performance factor give the level of TT performance to local petroleum industry through the TT process. Realizing the study objective would require requesting the petroleum industry input through questionnaire surveys in pilot, main studies, and validated by case studies. For the main study, 300 questionnaire surveys were distributed and 205 were collected, offering a response rate of 68 per cent. Statistical analysis techniques, including, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were used to examine the survey data. Analysis resulted in a TT model encompassing three TT enabling factors, namely, government support, host characteristics, technology learning capability, and the resultant performance factor named TT performance. The baseline formulation for standardization of TT measurement in the petroleum industry was undertaken using series of measurements. Case studies from three Libyan companies involved with foreign partners were applied to validate the standardization. The study provided evidence that the UK is the leading petroleum investor in Libyan petroleum industry. However, at TT performance perspective, German and Italian corporations have the leading edge on TT petroleum projects. TT model was created to help both researchers and practitioners to understand the TT process in petroleum industry. The model provided an evident design on main variables influenced TT issues. The structural model consisted of four factors and five paths, representing the interrelationships between the four enabling and one outcome factor. Positively, the research results empirically validated that factors referring to technology learning capability, technology characteristics, and technology support could be incorporated to evaluate the TT performance.